Implementation of The "Gemilang" Program in Improving The Quality of Public Services at The Population and Civil Registration Office of Lamongan District - AHMAD SHOLIKIN; Dwi Oktaviana (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
Implementation of the GEMILANG Program in Improving the Quality of Public Services at the Population and Civil Registration Office of Lamongan Regency. Thesis Government Studies Program, Faculty of Social and Political Sciences, Darul Ulum Islamic University Lamongan. This study examines the implementation of the GEMILANG Program in improving the quality of public services at the Population and Civil Registration Office of Lamongan Regency. The purpose of this study was to determine the improvement of the quality of pubic services at the population and civil registration office of Lamongan district, namely through the GEMILANG program. The type of research used is qualitative with a descriptive approach, namely by describing the research results and analyzing them so that the results are obtained and then concluding them. This research uses data sources derived from scientific journals, book literature, official websites. In this study, researchers used data collection methods with interviews, observations, document archives, and documentation to see the results of research and discussion. The results showed that the GEMILANG Program services can be said to be in accordance with the criteria of Edward George III's theory, namely communication, resources, disposition, and bureaucratic structure. Thus obtaining the result that the GEMILANG Program services carried out by the Population and Civil Registration Office of Lamongan Regency are quite effective, the implementation is beneficial for the community and the organization and the GEMILANG program will be carried out continuously.